A first evaluation of the usefulness of feathers of nestling predatory birds for non-destructive biomonitoring of persistent organic pollutants - Igor Eulaers; Adrian Covaci; Dorte Herzke; Marcel Eens; Christian Sonne; Truls Moum; Lisbeth Schnug; Sveinn Are Hanssen; Trond Vidar Johnsen; Jan Ove Bustnes; Veerle L.B. Jaspers (Environment International, 2011)
In previous studies, feathers of adult predatory birds have been evaluated as valid non-destructive biomonitor matrices for persistent organic pollutants (POPs). In this study, we assessed for the first time the usefulness of nestling raptor feathers for non-destructive biomonitoring of POPs. For this purpose, we collected body feathers and blood of nestlings from three avian top predators from northern Norway: northern goshawks (Accipiter gentilis), white-tailed eagles (Haliaeetus albicilla) and golden eagles (Aquila chrysaetos). We were able to detect a broad spectrum of legacy POPs in the nestling feathers of all three species (Σ PCBs: 6.78–140 ng g−1; DDE: 3.15–145 ng g−1; Σ PBDEs: 0.538–7.56 ng g−1). However, these concentrations were lower compared to other studies on raptor species, probably due to the aspect of monitoring of nestlings instead of adults. Besides their analytical suitability, nestling feathers also appear to be biologically informative: concentrations of most POPs in nestling feathers showed strong and significant correlations with blood plasma concentrations in all species (p<0.050; 0.775<r<0.994). In addition, the reported correlations between feathers and blood plasma were much higher than those previously reported for adult individuals. Accumulation profiles and species-specific differences were in accordance with other toxicological studies on avian species and generally in agreement with the specific ecology of the studied species. In summary, our results indicate that the use of nestling feathers of northern raptors may be a valid and promising non-destructive biomonitoring strategy for POPs in their ecosystems. Keywords: Biomonitor, Blood, Feather, Golden eagle, Nestling, Northern goshawk, OCP, PBDE, PCB, POP, White-tailed eagle